Marketplace Shopee Sebagai Media Komunikasi Pemasaran Toko Fajri Craft - Chayono, Idrian; Narti, Sri; Dianthi, Martha Heriniazwi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Marketplace is a platform that facilitates online business transactions such as buying and selling goods or services online between sellers and buyers. This study aims to determine the Shopee Marketplace as a marketing communication medium for Fajri Craft Shop. This research is a qualitative descriptive research. Based on the theory used is integrated marketing communication (IMC) according to Kotller and Armstrong. The results of this study found that. First, advertising, Fajri Craft Shop utilizes the Sponsored Ads feature discount and promo features, such as flash sales, cashback and free shipping to attract more buyers. Second, sales promotion, Fajri Craft Shop uses promotional strategies such as big discounts, vouchers, free shipping, and bundling which are considered very effective in attracting buyers and increasing sales. Third, public relations, Fajri Craft Shop’s relationship with customers shows that the communication approach that focuses on active and responsive interaction, this reflects an excellent strategy in building strong and positive relationships with customers. Fourth, personal selling, in making sales, Fajri Craft Shop cooperates with influencers and affiliates. Fifth, direct marketing, the direct marketing strategy implemented by Fajri Craft Shop in the marketplace is very effective in attracting customer attention, namely by utilizing advertising features, participating in promotions, creating quality content, and providing responsive customer service Thus, an integrated marketing communication (IMC) strategy can be an effective step in utilizing the shopee marketplace as a marketing communication medium..